Perlindungan Hukum Terhadap Konsumen dalam Penggunaan Kontrak Elektronik dengan Klausula Eksonerasi pada E-Commerce - Patricia, Tiara; Adam, Richard C. (UNES Law Review, 2023)
The current development of digital technology has significantly influenced the way humans conduct transactions in their daily lives, including in commercial activities or buying and selling. This research is conducted to analyze legal issues concerning legal protection for consumers bound by electronic contracts with exoneration clauses. The research method employed is normative or doctrinal. The government has ensured consumer protection by establishing legal provisions through Law Number 8 of 1999, which regulates the prohibition of including exoneration clauses by business entities. Consequently, businesses that include exoneration clauses can be sentenced to criminal law. However, in practice, law enforcement in consumer protection has not been as effective as it should be due to the presence of business entities, specifically e-commerce, that include exoneration clauses in standardized electronic contracts. Furthermore, based on the case of Angga Saputra Ariyanto, e-commerce as a business entity fail to fulfill their obligation to provide compensation. Therefore, it is necessary to address this issue through government oversight of standard clauses that involve the transfer of responsibility.